Association of peripheral neuropathy with circulating advanced glycation end products, soluble receptor for advanced glycation end products and other risk factors in patients with type 2 diabetes. Issue 8 (November 2014) - Aubert, C.E.; Michel, P.‐L.; Gillery, P.; Jaisson, S.; Fonfrede, M.; Morel, F.; Hartemann, A.; Bourron, O.
Abstract Background The pathogenesis of diabetic peripheral neuropathy remains uncertain and nonenzymatic glycoxidation is one of the contributing mechanisms. The aim of this study was to assess the respective relationship of diabetic peripheral neuropathy with glycoxidation, compared with other identified risk factors, in patients with type 2 diabetes. Methods We included 198 patients with type 2 diabetes and high risk for vascular complications. Circulating concentrations of three advanced glycation end products (carboxymethyllysine, methyl‐glyoxal‐hydroimidazolone‐1, pentosidine) and of their soluble receptor (sRAGE) were measured. Peripheral neuropathy was assessed by the neuropathy disability score and by the monofilament test and defined as either an abnormal monofilament test and/or a neuropathy disability score ≥6. Multivariate regression analyses were performed adjusting for potential confounding factors for neuropathy: age, gender, diabetes duration, current smoking, systolic blood pressure, waist circumference, height, peripheral arterial occlusive disease, glycated haemoglobin, estimated glomerular filtration rate and lipid profile. Results Prevalence of peripheral neuropathy was 20.7%. sRAGE and carboxymethyllysine were independently and positively associated with the presence of peripheral neuropathy. No significant association was found between peripheral neuropathy and methyl‐glyoxal‐hydroimidazolone‐1 or pentosidine. Waist circumference, height and peripheral arterial occlusive disease were independently associated with peripheral neuropathy. Conclusions Carboxymethyllysine and sRAGE were independently associated with peripheral neuropathy in patients with type 2 diabetes. Although the conclusions are limited by the absence of a healthy control population, this study confirms the relationship between advanced glycoxidation and diabetic peripheral neuropathy, independently of other risk factors. Copyright © 2014 John Wiley & Sons, Ltd.